2018
DOI: 10.3390/molecules23071637
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Improves Skin Flap Viability in Rats: A Preliminary In Vivo and In Vitro Investigation

Abstract: Selective estrogen receptor modulators (SERMs) have been developed to achieve beneficial effects of estrogens while minimizing their side effects. In this context, we decided to evaluate the protective effect of genistein, a natural SERM, on skin flap viability in rats and in a series of in vitro experiments on endothelial cells (migration, proliferation, antioxidant properties, and gene expression profiling following genistein treatment). Our results showed that administration of genistein increased skin flap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The results showed that the nanoemulsion with isoflavone-containing hydrolyzed soybean extract improved skin permeability and the nonhydrolyzed soybean extract containing isoflavone improved skin retention. The antioxidant effect was higher in nanoemulsions containing isoflavone-containing soybean extract than in those of pure isoflavones (Table S8) [244]. This suggests that the nanoemulsion containing isoflavone-rich soybean extract can be used as a topical formulation to protect the skin from UVA/UVB oxidative damage.…”
Section: Reduced Inflammation and Skin Cell Protection In Wound Tissuementioning
confidence: 95%
See 1 more Smart Citation
“…The results showed that the nanoemulsion with isoflavone-containing hydrolyzed soybean extract improved skin permeability and the nonhydrolyzed soybean extract containing isoflavone improved skin retention. The antioxidant effect was higher in nanoemulsions containing isoflavone-containing soybean extract than in those of pure isoflavones (Table S8) [244]. This suggests that the nanoemulsion containing isoflavone-rich soybean extract can be used as a topical formulation to protect the skin from UVA/UVB oxidative damage.…”
Section: Reduced Inflammation and Skin Cell Protection In Wound Tissuementioning
confidence: 95%
“…Genistein improves the viability of skin flaps (unlike skin transplantation, a tissue is supplied with blood by itself, and because the skin is moved while securing blood circulation without dividing part of the graft, the surgery is difficult to perform and there could be severe sequelae if it fails) [244]. A study with experimental mice was conducted to investigate the viability of genistein, a natural selective estrogen receptor modulator (SERM) of skin flaps, for its antioxidant properties on endothelial cells, and whether necrosis could be prevented after blood flow damage.…”
Section: Reduced Inflammation and Skin Cell Protection In Wound Tissuementioning
confidence: 99%
“…Notably, the anti-inflammatory effect of genistein may also be related to its antioxidative properties. It was shown that treatment of human keratinocytes and fibroblasts with genistein could prevent skin aging via modulation of glutathione (GSH) content and reactive oxygen species (ROS) release, endothelial/inducible (e/i)NOS dependent NO release, matrix metalloproteinases (MMPs) expression, and mitochondria membrane potential through mechanisms involving p38 MAPK, Akt and extracellular signal-regulated kinases 1/2 (ERK1/2) as downstream signaling associated with ERs and GPR30 [58], as well as by increasing superoxide dismutase (SOD) activity and B-cell lymphoma 2 (Bcl-2) expression in endothelial cells [59,60]. Importantly, as was shown in an in vivo study where OVX mice were co-treated with ER antagonist, the ameliorative effect of genistein on the inflammatory stage of wound healing seems to be independent of ER-mediated signaling.…”
Section: Inflammatory Phase and Oxidative Stressmentioning
confidence: 99%
“…In low doses (0.01-50 µM), genistein was shown to exert a positive effect on the secretion of bFGF, EGF, angiogenin, angiopoietin-2, MMP-9, and uPA receptor in HUVECs [88]. Interestingly, co-treatment of endothelial cells with VEGF and genistein at low concentrations (100 nM) showed a synergic effect on the upregulation of six angiogenesis promoting genes-MMP14, VEGF-A, CTGF, C-X-C motif chemokine 5 (CXCL5), IL-6 and integrin β3 (ITGB3)-as well as three angiogenesis inhibiting gene expressions-Collagen Type XVIII Alpha 1 Chain (COL18A1), Tissue inhibitor of metalloproteinases (TIMP)-2, and TIMP-3 [59]. Therefore, we also used Western blot to confirm changes in gene expressions on the protein level.…”
Section: Angiogeneismentioning
confidence: 99%
See 1 more Smart Citation